THE EFFECT OF DIGITAL LEADERSHIP, LEADER MEMBER EXCHANGE AND INNOVATION CAPABILITY ON EMPLOYEE PERFORMANCE AT THE REGIONAL SECRETARY'S OFFICE OF BIMA DISTRICT - Dian Ernawati; Nurul Huda; Julaiha (Program Studi Akuntansi Universitas Islam Lamongan, 2025)
This study aims to determine the effect of Digital Leadership, Leader Member Exchange and Innovation Capability on Employee Performance. In this study, the method used is a quantitative approach method, and the instrument used is a Likert scale questionnaire . The results of this study indicate that Digital Leadership and Leader Member Exchange do not have a significant effect on Employee Performance, and Innovation Capability has a significant effect on Employee Performance. And simultaneously Digital Leadership, Leader Member Exchange and Innovation Capability have a significant effect on Employee Performance at the Bima Regency Regional Secretary's Office .